2020
DOI: 10.4149/neo_2020_190730n687
|View full text |Cite
|
Sign up to set email alerts
|

miR-193a-5p suppresses cell proliferation and induces cell apoptosis by regulating HOXA7 in human ovarian cancer

Abstract: Ovarian cancer is one of the most common malignancies in women in the world. MicroRNAs (miRNAs) were identified as a group of regulators that played important roles in the progression of cancer development. The main purpose of this study was to investigate the functional mechanism of microRNA-193a-5p (miR-193a-5p) in human ovarian cancer. Quantitative real-time polymerase chain reaction (qRT-PCR) was used to detect the RNA levels of miR-193a-5p and homeobox genes A7 (HOXA7). Western blot assay was performed to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 35 publications
0
7
0
Order By: Relevance
“…HOXA subfamily genes are critical regulators of cancer metastasis. Homeobox 7 (HOXA7), a member of the HOXA subfamily, has been shown to function as an oncogene and contributes to malignant behaviors in various human cancers, including hepatocellular carcinoma [ 12 ], laryngeal squamous cell cancer [ 13 ], and ovarian cancer [ 14 ]. However, the function of HOXA7 in CRC metastasis is poorly understood.…”
Section: Introductionmentioning
confidence: 99%
“…HOXA subfamily genes are critical regulators of cancer metastasis. Homeobox 7 (HOXA7), a member of the HOXA subfamily, has been shown to function as an oncogene and contributes to malignant behaviors in various human cancers, including hepatocellular carcinoma [ 12 ], laryngeal squamous cell cancer [ 13 ], and ovarian cancer [ 14 ]. However, the function of HOXA7 in CRC metastasis is poorly understood.…”
Section: Introductionmentioning
confidence: 99%
“…To date, multiple miRNA types have been identified as participating in OC treatment. Wang et al found that miR-193a-5p targeting HOXA7 regulation inhibited cell proliferation and induced cell apoptosis in human OC (11). Paliwal et al revealed that miR-22 and miR-21 could be validated as good diagnostic biomarkers for the early detection of OC (12).…”
Section: Introductionmentioning
confidence: 99%
“…When the cells grow to the logarithmic growth phase, trypsin digestion to collect the cells, use DMEM medium to dilute the cells to 1x10 6 · ml -1 , inoculate the cells into a 6-well plate (1000 cells / well), after 24 hours of culture, Incubate for 10-14 days with 1% 0.33% BME agar medium with or without DAPT (0-1 μM) in 10% FBS [15] . Cell colonies were counted under the microscope using Image-Pro Plus software (Media Cybernetics, USA).…”
Section: Soft Agar Colony Formation Test and Clone Formation Testmentioning
confidence: 99%
“…DAPT (DAPT) is a γ-secretase substrate that can act as a γ-secretase inhibitor to indirectly inhibit Notch signal transduction in autoimmune and lymphoproliferative diseases including Alpine disease and lupus erythematosus (SLE) The medicinal effect is significant, and it also plays an important role in the growth of various cancer cells, angiogenesis and differentiation of human induced pluripotent stem cells (hIPSC) by inhibiting Notch signaling [14][15] . The purpose of this study was to explore the effect of DAPT on hepatocellular carcinoma in vivo and in vitro, and the effect of DAPT on the anticancer activity of olaparib, and to preliminary explore the potential mechanism of DAPT's antitumor effect.…”
mentioning
confidence: 99%